2015
DOI: 10.1088/0952-4746/36/1/37
|View full text |Cite
|
Sign up to set email alerts
|

Staff lens doses in interventional urology. A comparison with interventional radiology, cardiology and vascular surgery values

Abstract: The purpose of this work is to evaluate radiation doses to the lens of urologists during interventional procedures and to compare them with values measured during interventional radiology, cardiology and vascular surgery. The measurements were carried out in a surgical theatre using a mobile C-arm system and electronic occupational dosimeters (worn over the lead apron). Patient and staff dose measurements were collected in a sample of 34 urology interventions (nephrolithotomies). The same dosimetry system was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…In contrast, the heads of taller scrub nurses may extend above the lead glass, especially when the doctor may position it lower, allowing for scattered radiation to project above the shield and impinge on the cranium of the scrub nurse. It has been demonstrated that doses during endovascular procedures may be higher than that of coronary 32,33 and this may explain why there is a marked difference between both the height-dose relationship when comparing coronary procedures to vascular (Fig. 4), but again fails to account for the positive height-dose relationship for scrub and scout nurses during procedures imaging the chest, which largely constitutes cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the heads of taller scrub nurses may extend above the lead glass, especially when the doctor may position it lower, allowing for scattered radiation to project above the shield and impinge on the cranium of the scrub nurse. It has been demonstrated that doses during endovascular procedures may be higher than that of coronary 32,33 and this may explain why there is a marked difference between both the height-dose relationship when comparing coronary procedures to vascular (Fig. 4), but again fails to account for the positive height-dose relationship for scrub and scout nurses during procedures imaging the chest, which largely constitutes cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, Peruzzo Cornetto et al tabulated data for 23 procedures in an Italian hospital, Compagnone et al published data from a different Italian hospital for nine interventional procedures, Dauer et al published P KA data for 43 interventional fluoroscopy procedures at a single U.S. institution, Bundy et al did the same for 12 procedures at a different U.S. medical center, Erskine et al published P KA data for 32 interventional fluoroscopy procedures in Australia, Étard et al’s report contains data from France for 15 procedures, Pitton et al published data for 17 interventional vascular procedures at a German hospital, Schmitz et al reported data on biliary interventions at 23 different facilities, and Ruiz‐Cruces et al reported data for seven interventional procedures performed at eight hospitals in Spain. Many other published studies were also consulted to estimate one or more of P KA , E , and DC E …”
Section: Resultsmentioning
confidence: 99%
“…Many other published studies were also consulted to estimate one or more of P KA , E, and DC E . 7,11,12,14,15,[17][18][19]21,[24][25][26][27][29][30][31][32][33][34][35][36][37][38][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] Published values of P KA are included in Table I. Table II provides data for E and Table III provides data for DC E .…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been shown that typically 1 Gy • cm 2 of KAP to the patient results in an estimated average dose to the lens of the eye of 10 μSv due to scatter dose at a C-arm (Leyton et al 2016). By applying radiation protection measures, the eye dose due to scattered radiation can be reduced by up to 6%, at a C-arm (Vano et al 2016). Variations in fluoroscopy time and KAP were observed (Table 2), which were probably due to the complexity of the procedure and the experience of the cardiologist, because similar systems were used for all measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The key components of the implemented training actions were radiation protection, optimizing of work practice, eye lens doses monitoring and reduction. Training in radiation protection is the most desirable and successful action to reduce occupational doses (Vano et al 2016). Additionally, for clinicians who were not interested in any technical details a simplified version of the training material was developed as a mobile app that provides a higher level of outreach than more detailed training material.…”
Section: Methodsmentioning
confidence: 99%